FREQUENCY OF METABOLIC SYNDROME IN PATIENTS WITH PSORIASIS - Raza, Musarrat Hussain; Iftikhar, Nadia; Mashhood, Asher Ahmed; Hamid, Muhammad Ammar Bin; Rehman, Farhat; Tariq, Shahan (Journal of Ayub Medical College Abbottabad, 2021)
Background: Psoriasis is a non-communicable, long-lasting disorder of the skin comprising various immunological inflammatory changes. Increasing evidence suggests that psoriasis is closely related to multiple organ systems, potentially arising due to underlying co-morbid conditions such as diabetes, hypertension, dyslipidaemia and obesity. Aim of this study was to know the frequency of metabolic syndrome in psoriasis patients. Methods: This cross-sectional study was conducted from May to November 2020 in a Tertiary-care hospital. 80 patients diagnosed with psoriasis were selected using non-probability consecutive sampling. Informed written consent was obtained from each patient and a questionnaire was filled. Blood pressure, waist circumference, body surface area covered by psoriasis, Psoriasis Area Severity Index were recorded on initial visit. Fasting blood sugar, serum triglyceride and HDL cholesterol levels were advised. Patients were diagnosed to have metabolic syndrome if ‰¥3 out of 5 criteria for the modified version of National Cholesterol Education Program Adult Panel III were met. Results: There were 62 male and 18 female patients. A total of 39 patients (48.8%) met the criteria for metabolic syndrome. Amongst these, 26/62 (41.9%) males vs 13/18 (72.2%) females fulfilled the criteria. The mean BMI of males was 26.0 while those of females was 28.3, comparison of which demonstrated a noteworthy difference (p=0.04). A statistically significant (p=0.038) positive correlation (r) of 0.233 was observed between body surface area and BMI. Conclusion: Metabolic syndrome is seen frequently in patients of Psoriasis. Female patients have a significant frequency of metabolic syndrome and tend to have a higher BMI than males.